Special Focus Introduction: Refugee Voices in Contemporary Literature - Kathryn Sederberg; Rebekah Slodounik (Studies in 20th & 21st Century Literature, 2025)
Special Focus Introduction: Refugee Voices in Contemporary Literature
Keywords: refugees; narrative; refugee narratives; forced migration; displacement; critical refugee studies